Infrared Thermography as a Method for Energy Absorption Evaluation of Metal Foams. (2016) - Krstulović-Opara, Lovre; Vesenjak, Matej; Duarte, Isabel; Ren, Zoran; Domazet, Željko
Abstract: Cellular structures are inhomogeneous materials where tracing the yielding process is of particular importance in evaluating the impact energy absorbing capabilities. This paper gives an overview of using Infrared thermography to visualize and record the yielding process including development of plastification zones, slide-lines formation, densification and fracture of cellular materials. Open-cell metal foams, open-cell foams with cell filler, closed-cell foams, Advanced Pore Morphology (APM) foam elements and structural tubes with closed-cell foam filler subjected to dynamic loading conditions were evaluated. It is shown how different structures can be characterized by thermal imaging of observed metal foams. Presented non-destructive approach is based on middle-wave cooled thermal detector capable of acquiring clear thermal images at high frequencies. Thermal images, equivalent to strain distribution, improve detecting and evaluating overall energy transfer process occurring at cellular structures used as energy absorbers. The infrared thermography proved to be an effective toll to observe the deformation modes and collapse of different types of metallic foams.